Unilateral hypopyon associated acute syphilitic posterior placoid chorioretinitis: Unusual presentation leading to HIV diagnosis. (July 2021) - Kumar, Ashok; Kumar, Poninder; Mishra, Sanjay Kumar; Goyal, Sumit
Syphilis has a wide variety of ocular presentations such as anterior or posterior uveitis, chorioretinitis, retinal vasculitis, retinitis, perineuritis, papillitis, retrobulbar neuritis, optic atrophy and optic nerve gumma. Therefore, it is recommended to test every patient with ocular inflammation for syphilis. It is, however, a relatively rare cause of uveitis in HIV disease. A few studies suggested that HIV contributes to the ocular manifestations of syphilis and HIV co-infection in approximately 30%. Acute syphilitic posterior placoid chorioretinopathy is a rare ocular manifestation in immune-competent patients characterised by the development of a deposit in the outer retina. We describe an unusual such presentation with hypopyon.